Effects of Potassium Carbonate and Ethyl Oleate Pretreatments on Quality and Drying Rate of Green Raisins - Mohmand, Samiullah; Salari, Hamid; Rahmani , Abdurahman (Journal of Natural Sciences – Kabul University, 2025)
The production of green raisins holds significant economic value in Afghanistan; however, traditional drying methods often results prolonged drying time and reduced product quality. The main objective of the research was to shorten drying duration, and enhance the overall quality of green raisins. This study was carried out in 2024 at Kabul University's Agriculture Faculty research farm using a Factorial Complete Randomized Design (F-CRD) with 12 treatments and 3 replications. During this period, quantitative, qualitative, and visible disease parameters were evaluated. It was observed that the third treatment (1.5% Potassium Carbonate + 2% Ethyl Oleate) shortened drying time and improved the appearance, color, flavor, taste, texture, overall acceptance, and disease resistance of raisins. Based on the findings, it is recommended that farmers and stakeholders involved in raisin production use the mentioned concentration to obtain high-quality green raisins in a shorter period of time.